Electronic and structural properties of La0.4Sr0.6Ti1-yCoyO3±d electrode materials for symmetric SOFC studied by hard X-ray Absorption Spectroscopy - Napolitano, Federico Ricardo (2013)
We present combined Synchrotron X-ray Absorption Near Edge Spectroscopy (XANES) and Extended X-ray Absorption Fine Structure (EXAFS) study of La0.4Sr0.6Ti1yCoyO3d (0 <=y <= 0.5), which are promising electrode materials for symmetric solid oxide fuel cells. The measurements were performed at room temperature at the Ti and the Co K-edges in order to determine the local structural and electronic changes around the two transition metals. We find that Ti remains in a higher formal valence (around 4þ) independent of the Co concentration. In contrast to this, dramatic and systematic changes are observed for the Co as a function of y.We conclude that the stability of the Ti4þ triggers the A-site deficiency in our samples and predicts that oxygen vacancies are much more easily formed at large Co content, which in turn will greatly enhance the performance as electrode material.